Synthesis of Arylpiperazine Derivatives as Protease Activated Receptor 1 Antagonists and Their Evaluation as Antiproliferative Agents - Zotti, Andrea I.; Di Gennaro, Elena; Corvino, Angela; Frecentese, Francesco; Magli, Elisa; Perissutti, Elisa; Cirino, Giuseppe; Roviezzo, Fiorentina; Terranova-Barberio, Manuela; Iannelli, Federica; Caliendo, Giuseppe; Santagada, Vincenzo; et al. (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Protease activated receptor-1 (PAR1) is a G-coupled receptor activated by α-thrombin and other proteases. Several reports have demonstrated the PAR1 involvement in tumorigenesis and tumor progression. In order to investigate on potential use of PAR1 antagonists as antiproliferative agents. Aims: We have identified a series of arylpiperazine derivatives acting as PAR1 antagonists; the selected molecules have been evaluated for their antiproliferative properties. Method: All the compounds inhibited the growth of a panel of cell lines expressing PAR1; two of them, compounds 13 and 15, were able to inhibit, in a dose dependent manner, the growth of the selected cell lines with the lowest IC50 values, and were further characterized to define the mechanism responsible for the observed antiproliferative effect. Result: This study directed us to the identification of two interesting leads that may help to further validate PAR1 as an important therapeutic target for cancer treatment.
Keywords: arylpiperazines